2022
DOI: 10.2147/prbm.s354083
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well-Being During the Second Wave of COVID-19 Pandemic: The Mediation Role of Generalized Anxiety

Abstract: The outbreak of the COVID-19 has largely impacted individuals' health and lifestyles. This study aimed to investigate people's psychological well-being during the second phase of the COVID-19 pandemic. Methods: We selected six indicators of psychological well-being: fear of COVID-19, loneliness, social interaction anxiety, generalized anxiety, PTSD, and depression. A sample of 231 Italian participants (56.3% women), with a mean age of 32.7 (SD=12.61), completed an online survey from February to March 2021, dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…In the first wave, the national lockdown involved the suspension of essential services (e.g., provision of legal information and psychosocial support, administrative procedures related to occupational and educational integration) which caused elevated distress and conflicts within the residential care communities (CIR, 2020). After a short period during the summer when most restrictions were suspended, in the second wave—during which the current study was conducted—many were restored (e.g., online school lessons; social distancing measures and daily COVID‐19 testing at work/training), generating discomfort and loneliness (Faraci et al, 2022). Indeed, the tightening of the reception system conditions, the introduction of social distancing measures, and a general, COVID‐19 related precarity have likely contributed to an increased isolation and disruption of social relationships among UIMs, as well as to a greater anxiety over the uncertainty of their future (Barn et al, 2021; Oldroyd et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the first wave, the national lockdown involved the suspension of essential services (e.g., provision of legal information and psychosocial support, administrative procedures related to occupational and educational integration) which caused elevated distress and conflicts within the residential care communities (CIR, 2020). After a short period during the summer when most restrictions were suspended, in the second wave—during which the current study was conducted—many were restored (e.g., online school lessons; social distancing measures and daily COVID‐19 testing at work/training), generating discomfort and loneliness (Faraci et al, 2022). Indeed, the tightening of the reception system conditions, the introduction of social distancing measures, and a general, COVID‐19 related precarity have likely contributed to an increased isolation and disruption of social relationships among UIMs, as well as to a greater anxiety over the uncertainty of their future (Barn et al, 2021; Oldroyd et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The fear of COVID-19 has triggered the anxiety of undergraduates ( Ye et al, 2020 ), and during the epidemic, there are fewer ways and channels to alleviate or eliminate anxiety than before. In this case, undergraduates are more likely to have a sense of helplessness and hopelessness, which will lead to depression ( Abramson et al, 1978 ; Faraci et al, 2022 ). This proves that anxiety plays a mediating role between fear of COVID-19 and depression.…”
Section: Discussionmentioning
confidence: 99%
“…In the face of the negative influence of COVID-19, undergraduates will have anxiety such as nervous and worry at the beginning. However, as individuals have few active measures to take in the face of COVID-19, their anxiety cannot be alleviated, which will lead to depression (Faraci et al, 2022;Zhang et al, 2022). Therefore, the following hypothesis is proposed: H2: Anxiety plays a mediating role between the fear of COVID-19 and depression.…”
Section: The Mediating Effect Of Anxiety On the Relationship Between ...mentioning
confidence: 99%
“…10 This symptom is a complex response pattern characterized by feelings of palpitations, chest tightness, trembling, and fainting. 6,28,29 Spiritual well-being is the affirmation or maintenance of interpersonal relationships with God (religious well-being) and with oneself, society and the environment (extension well-being) to create happiness and life satisfaction. 21,30 Several studies have found a significant positive relationship between spiritual well-being and anxiety levels in mental illnesses, 16,31 is a crucial key that influences a psychological and mental health.…”
Section: Conceptual Frameworkmentioning
confidence: 99%